Penilaian Risiko Ergonomi Metode Rapid Entire Body Assessment pada Tenaga Kesehatan Puskesmas - Windu Yuli Widiastuti; Khomsiatun; Gozy Ajeng Retnowati; Eram Tunggul Pawenang (Buletin Keslingmas, 2026)
Musculoskeletal disorders (MSDs) are a major occupational health problem among healthcare workers in primary care facilities. Tlogosari Wetan Community Health Center has never conducted a systematic ergonomic risk assessment despite its healthcare workers performing various high-risk physical activities daily. Objective To identify ergonomic risk levels in work postures of healthcare workers at Tlogosari Wetan Community Health Center Semarang using the Rapid Entire Body Assessment (REBA) method and to formulate intervention recommendations based on the hierarchy of controls. Observational descriptive study with a cross-sectional design. Twenty healthcare workers from nine professions were observed using total sampling. Each respondent was assessed on one most representative work posture using the REBA worksheet covering all body segments (neck, trunk, legs, upper arm, lower arm, and wrist) without exclusion, alongside force/load, coupling, and activity scoring. 20 postures assessed (80% female respondents), REBA scores ranged from 3 to 11 (mean 5.50, SD 2.28; 95% CI: 4.43–6.57). Risk distribution: low risk 2 postures (10.0%), medium risk 15 postures (75.0%), high risk 2 postures (10.0%), very high risk 1 posture (5.0%). The highest score (REBA 11) was recorded during a joint wound care procedure performed by a nurse and a doctor. Dominant risk factors: excessive trunk and neck flexion (>20–60°) in 85% of postures, shoulder elevation in 75% of postures, and static-repetitive loading in 100% of postures. All observed postures required ergonomic attention. Staged interventions based on the NIOSH Hierarchy of Controls are recommended for immediate implementation: engineering controls (height-adjustable workstations, hi-low beds, ergonomic chairs, magnifying loupes), administrative controls (micro-breaks, task rotation), and PPE (wrist support, headlamp).